IMPLEMENTASI IDENTIFIKASI SISTEM METODE BLACK BOX PADA MOTOR DC MENGGUNAKAN CORRELATION ANALYSIS DAN MODEL ARX - Mangkusasmito, Fakhruddin; Tadeus, Dista Yoel; Subari, Arkhan (Gema Teknologi, 2020)
The identification system is a procedure to obtain a model of a system, then of the model will be validated to see the accuracy of the model is obtained, compared to the input-output results obtained from the experiments. In the identification system itself known two methods, the method of "non-parametric" and "parametric". On the other hand, DC motor is a type of motor that uses direct electric current to produce rotational mechanical energy and is widely used in various applications. In this study, input and output data acquisition will be performed on the Feedback brand DC motor, and the data will be processed so that the system model is obtained by the black box method. The data will then be processed with the help of MATLAB software. The input signal used in this experiment is Pseudorandom binary sequence (PRBS), which is used because it has a wide frequency range. The signal is generated by an arduino uno microcontroller. From the test results it was found that the validation of the non parametric system model with the correlation analysis method has a fitness value of = 83.19%, while the validation of the parametric system model with the least square ARX method has a fitness value of = 80.59%.